2016
DOI: 10.1038/srep36345
|View full text |Cite
|
Sign up to set email alerts
|

Boreal earliest Triassic biotas elucidate globally depauperate hard substrate communities after the end-Permian mass extinction

Abstract: The end-Permian mass extinction constituted the most devastating biotic crisis of the Phanerozoic. Its aftermath was characterized by harsh marine conditions incorporating volcanically induced oceanic warming, widespread anoxia and acidification. Bio-productivity accordingly experienced marked fluctuations. In particular, low palaeolatitude hard substrate communities from shallow seas fringing Western Pangaea and the Tethyan Realm were extremely impoverished, being dominated by monogeneric colonies of filter-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 75 publications
2
10
0
Order By: Relevance
“…3). The present data are consistent with previous studies indicating that this opportunistic group of encrusters flourished and became more abundant than other encrusters in the aftermaths of mass extinctions and biotic crises (Fraiser 2011; Zatoń and Krawczyński 2011; He et al 2012; Yang et al 2015; Zatoń et al 2016).…”
Section: Discussionsupporting
confidence: 93%
“…3). The present data are consistent with previous studies indicating that this opportunistic group of encrusters flourished and became more abundant than other encrusters in the aftermaths of mass extinctions and biotic crises (Fraiser 2011; Zatoń and Krawczyński 2011; He et al 2012; Yang et al 2015; Zatoń et al 2016).…”
Section: Discussionsupporting
confidence: 93%
“…Such a niche could have been advantageous (see Vinn, 2010a), providing protection against overgrowth and sediment covering, and lessening competition for suspended food in a higher tier. The microconchids in this setting had the ability to keep pace with the growth of encrusting algae and microbialite with which they were typically associated (e.g., Peryt, 1974;Burchette and Riding, 1977;Dreesen and Jux, 1995;Zatońet al, 2016b). Only such a growth mode allowed microconchids to develop primary frameworks (Vinn, 2010a).…”
Section: Discussionmentioning
confidence: 99%
“…Although the majority of microconchids were characterized by Spirorbis -like, planispirally coiled tubes, several genera produced unique morphologies. For example, some Carboniferous (Mississippian) species formed long, helically uncoiled tubes (e.g., Burchette and Riding, 1977), whereas the Lower Triassic Spathioconchus Zatoń et al, 2016b formed straight, trumpet-like tubes (Zatoń et al, 2016b) and the Permian Helicoconchus Wilson, Vinn, and Yancey, 2011 had long, helically uncoiled tubes that showed budding (Wilson et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the information of shape/arrangement of microstructures and element distributions on fossils can be extracted by ESEM so that to provide paleogeographic environmental data of stratigraphic formation for determining geological age and stratigraphic correlation. Many studies about fossils based on ESEM have hence made significant contributions to cultural heritage conservation . For example, McPherron et al observed the fossilized bones under ESEM and found unambiguous stone‐tool cut marks for flesh removal and percussion marks for marrow access.…”
Section: Recent Applicationsmentioning
confidence: 99%